Polyscore of autonomic parameters for risk stratification of the elderly general population: the Polyscore study. Issue 5 (4th December 2020) - Steger, Alexander; Dommasch, Michael; Müller, Alexander; Sinnecker, Daniel; Huster, Katharina M; Gotzler, Teresa; Gotzler, Othmar; Hapfelmeier, Alexander; Ulm, Kurt; Barthel, Petra; Hnatkova, Katerina; Laugwitz, Karl-Ludwig; et al.
Abstract: Aims: Present society is constantly ageing and elderly frequently suffer from conditions that are difficult and/or costly to treat if detected late. Effective screening of the elderly is therefore needed so that those requiring detailed clinical work-up are identified early. We present a prospective validation of a screening strategy based on a Polyscore of seven predominantly autonomic, non-invasive risk markers. Methods and results: Within a population-based survey in Germany (INVADE study), participants aged ≥60 years were enrolled between August 2013 and February 2015. Seven prospectively defined Polyscore components were obtained during 30-min continuous recordings of electrocardiogram, blood pressure, and respiration. Out of 1956 subjects, 168 were excluded due to atrial fibrillation, implanted pacemaker, or unsuitable recordings. All-cause mortality over a median 4-year follow-up was prospectively defined as the primary endpoint. The Polyscore divided the investigated population ( n = 1788, median age: 72 years, females: 58%) into three predefined groups with low ( n = 1405, 78.6%), intermediate ( n = 326, 18.2%), and high risk ( n = 57, 3.2%). During the follow-up, 82 (4.6%) participants died. Mortality in the Polyscore-defined risk groups was 3.4%, 7.4%, and 17.5%, respectively ( P < 0.0001). The Polyscore-based mortality prediction was independent of Framingham score, diabetes, chronic kidney disease, and major stroke and/or myocardial infarction history. It was particularly effective in those aged <75 years ( n = 1145). Conclusion: The Polyscore-based mortality risk assessment from short-term non-invasive recordings is effective in the elderly general population, especially those aged 60–74 years. Implementation of a comprehensive Polyscore screening of this age group is proposed to advance preventive medical care.